Use of tennis ball as a media to improve the shot put of XI grader in social major - Gunawan Ragil Saputra (PHEDHERAL, 2022)
The aims of this study were 1) to describe the use of tennis balls in the shot put skills of students in Class XI IPS 1 SMA N 1 Cilacap in Semester 1 of the 2022/2023 academic year and 2) to analyze the shot put skills of students in XI IPS 1 SMA N 1 Cilacap in Semester 1 of the 2022/2023 Academic Year which was increased by the use of tennis balls as media. This research is a Class Action Research (classroom action research). The research location was in Class XI IPS 1 SMA N 1 Cilacap, Cilacap Selatan District, Cilacap Regency. The time of the research was from early August to the third week of October 2022. The research subjects were 36 students of Class XI IPS 1 SMA N 1 Cilacap, Cilacap Selatan District, Cilacap Regency for the 2022 Academic Year. The research data is learning activities. Sources of research data are students. The data collection tool is the result of observing the basic techniques of shot put and documentation during learning. Data analysis techniques were carried out by qualitative data analysis and quantitative data analysis. The research procedure is action with a Cycle Model which consists of four stages, namely Planning, Action, Observation and Reflection. The results of the study are 1) the use of tennis ball media in the shot put skills of students of Class XI IPS 1 SMA N 1 Cilacap in Semester 1 of the Academic Year 2022/2023 is to help students carry out the basic shooting technique (the technique of holding bullets, the technique of placing bullets and the technique of repelling bullets) to the fullest and 2) the shooting skills of students of Class XI IPS 1 SMA N 1 Cilacap in Semester 1 of the 2022 Academic Year /2023 which increases with the use of tennis ball media. This is proven by the analysis of the results of observations in the Initial Conditions, Cycle I and Cycle II. The average score of students' shot put skills in the Initial Conditions was 63.64, in Cycle I it became 72.5, and increased significantly in Cycle II it reached 78.48.